Jewish forced labor under the Nazis economic needs and racial aims, 1938-1944 - Gruner, Wolf 1960- (Cambridge University Press, 2006)
Forced labor was a key feature of Nazi anti-Jewish policy and shaped the daily life of almost every Jewish family in occupied Europe. This book systematically describes the implementation of forced labor for Jews in Germany, Austria, the Protectorate, and the various occupied Polish territories. As early as the end of 1938, compulsory labor for Jews had been introduced in Germany and annexed Austria by the labor administration. Similar programs subsequently were established by civil administrations in the German-occupied Czech and Polish territories. At its maximum extent, more than one million Jewish men and women toiled for private companies and public builders, many of them in hundreds of now often-forgotten special labor camps. This study refutes the widespread thesis that compulsory work was organized only by the SS, and that exploitation was only an intermediate tactic on the way to mass murder or, rather, that it was only a facet in the destruction of the Jews